МАРГИНАЛЬНЫЕ ФОРМЫ РЕЧИ (Филологические заметки, 2019)
This article needs to overcome a certain difficult concepts: marginal forms of spoken language, area of their function, main characteristics, and specific nature of genre.
Keywords: marginal forms, unintelligible language, glossolalia